Hitomaro and the Birth of Japanese Lyricism - Levy, Ian Hideo, 1950- (Book collections on Project MUSE., 1984)
Professor Levy explores the ritual origins of Japanese verse, the impact of Chinese and Korean literary influence on the seventh-century Court, and the rhetorical deification of the imperial family as the condition under which Hitomaro would begin his career as a Court poet. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.